Neuroscience in Psychiatry towards an integrative and personalized medicine in the DSM-V: a proposal - Erick Emmanuel Pérez Solís; Carlos Augusto Novo Olivas (CAEN, 2009)
In the last Century the concept of health and, with it, medical science, has suffered a profound, conceptual and ontological change. However, this revolution has not reached, in the same way the field of mental health. In the next pages it will be shown, taking Major Depressive Disorder as a model, how it is possible and necessary, for the field ofpsychopathology (behavior and "mental" functions: rational, executive, cognitive, emotional, etc.) the return to its medical origins, which will allow it to respond how the brain functions and its interactions with the rest of the organism and the environment, with the goal of obtaining patterns that will help us to define disease from an etiopathogenic point of view, so it would be possible to provide therapeutic options to theorgan in question. The time has come to ask if we have invented a science (psychiatry) that has little to do with reality, and to answer that, the creation of multicentric data bases is proposed, in which biological (not just brain based), social, personal, clinical, etc. variables are integrated, to finally obtain correlations that allow us a reclassification of brain pathology that would be useful to offer integral and personalized treatments.